The Pusan International Film Festival, South Korean cinema, and globalization. - Ahn, SooJeong (TransAsia--screen cultures., 2012)
This book provides a social, political and cultural exploration of the Pusan International Film Festival (PIFF) in South Korea that since its inception in 1996. By paying a particular attention to the organizers' use of an Asian regionalization strategy, the book reveals how the festival staked out a unique and influential position within a rapidly changing global landscape.